Pode o açaí (Euterpe precatoria Mart.) ser parte importante no desenvolvimento socioeconômico das famílias extrativistas no Acre, Brasil? - Elaine Lopes da Costa (2017)
The role of non-timber forest products (NTFPs) as a strategy to improve the livelihoods of family forests and conserve biodiversity is still a cause for debate. While some explore ways in which NTFPs can be part of a solution for the development and conservation of the Amazon (JARAMILO et al., 2017), other researchers point to the need for caution before taxing NTFPs as forest saviors (PERES et al., 2003). For NTFPs, we have a literature rich in "specific contexts", which reveal the enormous diversity and complexity of socioeconomic and economic systems, but this specific context is difficult to generalize and does not allow a broad view of how the dilemmas of extractivism in the Amazon can be approached on the landscape scale. Currently in the Amazon there are three main products of extractive rubber, Brazil nuts and açaí, the latter since the 90s dethroned the classics of vegetable extractivism (Brazil nuts and rubber), becoming the holder of greater production and income, it is a popular royalty that was consecrated as an energy drink. However, in the Amazonian Biome, the açaí is the king of the vegetal extractivism, but in the state of Acre who is at the top of the royalty of the extractivism is still the Brazil nuts. However, the açaí extractivism is on the rise and today is the second product of the vegetal extractivism in the state, is a curious position, since the extractive population acreana does not have tradition of collection of these fruits. In this work, we discuss how the market influences the life of forest families in the Amazonian state of Acre; we map the ecology partner of the extractive systems of açaí and model the ecology (palm density and productivity) and the socio economy (price, costs and income). To answer if the açaí can be an important part in the socioeconomic development of the extractive families acreanas. The results indicate that açaí can not only be an important part of the socio-environmental development strategy of the forest families in Acre, because the state has a highly favorable territory to the occurrence of palm trees and forests with high production potential and income of açaí. We indicate a set of measures involving government, research institutions and forest families, so that the exploitation of the açaí reaches its potential.The information treated in this work still light the yellow signal for the governmental initiatives, that must be thought like care so that it does not the transfer of this product from the socioeconomic of forest families to entrepreneurs